Penerapan Patient Safety Pada Masa Pandemi Covid-19 Di Ruang Interna Wanita RSUD Dr. M. Haulussy Ambon - Ira Sandi Tunny (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
BackgroundPatient safety(patient safety) itself is a system that creates patient care while in the hospital to make it safer and calmer. Where this system is attempted to be able to prevent injuries caused by mistakes when carrying out inappropriate actions. ObjectiveThis research is to describe the implementation of patient safety during the Covid-19 pandemic in the Women's Internal Room at RSUD dr. M. Haulussy Ambon. Methodor this research design uses a descriptive quantitative research design. The research population and sample were all patients in the Women's Internal Room, totaling 44 people with a sampling technique, namely total sampling. Resultsshows that all respondents have understood and implemented how to identify patients correctly, improve effective communication, increase the safety of drugs that need to be monitored, ensure the right location, right procedure and correct patient surgery, reduce the risk of health care-related infections and reduce the risk of injury due to the patient fell. From the results of this research, Conclusionthat the description of the implementation of patient safety in the Women's Internal Room at RSUD dr. M. Haulussy Ambon is in accordance with Patient Safety Goals.